2012
DOI: 10.1177/0363546512463344
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Follow-up Study on Clinical and Radiological Outcomes of Polyurethane Meniscal Scaffolds

Abstract: This study demonstrated that limited medial meniscal RD was present preoperatively but increased by 2 mm after scaffold implantation. Lateral RD was also present preoperatively but did not increase after scaffold implantation. Importantly, a strong negative correlation was found between the rim and postoperative medial RD; a thicker rim limited RD. However, in the lateral compartment, rim thickness did not correlate with RD because RD was already strongly present preoperatively. Finally, no correlations were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 29 publications
6
48
2
Order By: Relevance
“…De Coninck et al [5] discussed the occurrence and impact of radial meniscal extrusion after implantation of the same scaffold used in this study and found a significant correlation between the residual meniscal rim and post-operative displacement of the scaffold. The authors implied that a radial meniscal displacement limits the biomechanical effects of the meniscus itself and thus bearing the risk of development of osteoarthritis [5]. This theory is supported by the data presented by Gale et al [11] who found an association of meniscal subluxation with osteoarthritis.…”
Section: Discussionsupporting
confidence: 59%
“…De Coninck et al [5] discussed the occurrence and impact of radial meniscal extrusion after implantation of the same scaffold used in this study and found a significant correlation between the residual meniscal rim and post-operative displacement of the scaffold. The authors implied that a radial meniscal displacement limits the biomechanical effects of the meniscus itself and thus bearing the risk of development of osteoarthritis [5]. This theory is supported by the data presented by Gale et al [11] who found an association of meniscal subluxation with osteoarthritis.…”
Section: Discussionsupporting
confidence: 59%
“…It has been shown to restore the contact pressures to those of the intact knee and improve peak contact pressures and the mean contact area relative to the partially meniscectomized knee [4]. It has also demonstrated its safety and its efficacy at improving the functional status of previously meniscectomized patients in short-term clinical investigations [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…2). RD was defined as the distance between the tibial plateau and the outer edge of the meniscus/implant, and was measured in mm as described by De Coninck et al (2013). This distance was negative when the meniscus fells completely within tibial margins.…”
Section: Radial Displacementmentioning
confidence: 99%
“…Increased RD is associated with loss of the meniscus's chondroprotective effect, which can possibly lead to further degeneration and osteoarthritis (Gale et al, 1999). There are currently only available data on RD of artificial meniscal substitutes in supine non-weight-bearing conditions (De Coninck et al, 2013;Hirschmann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%